Advanced interactive visualization for CFD - Giles, M; Haimes, R (1990)
New ideas are presented for the visualization of computational fluid dynamics data. These include both unsteady two-dimensional and steady three-dimensional data on either structured or unstructured grids. In addition to presenting some specific algorithm advances, considerable attention is devoted to innovative interactive probes and the appropriate choice of program architecture and internal data structure. © 1990.